Project manager’s personality: traits and competencies - S. A. Titov; N. V. Titova (Вестник университета, 2024)
Expanding the project management application scope in different sectors of economy and social life spheres stimulates the search and use of project success new factors. Researchers and practitioners note that the personality of a project manager’s personality is a significant factor affecting the project management effectiveness. At the same time, the scientific literature has not developed a coherent picture explaining the elements and role of a project manager’s personality. In search of an answer to this question, the study, built as a scientific literature systematic analysis, reveals that a project manager’s personality manifests itself as a set of personal competencies. Among the most significant personality competencies, experts include result-orientedness, optimism, honesty, adaptability, creativity, and intuition. Project manager’s personal competencies act as the core of the project management competency model and significantly affect professional technical competencies, primarily leadership, communication, and emotional intelligence. The novelty of the results obtained lies in the streamlining and deepening of theoretical ideas about a project manager’s personality and its role in the project management competencies formation. The study results are recommended to be used in training programs development for project managers and personnel selection.